Beyond the dikes: an institutional perspective on governing flood resilience at the Port of Rotterdam - Eline Punt; Jochen Monstadt; Sybille Frank; Patrick Witte (Maritime Economics & Logistics, 2022)
Seaports, infrastructural nodes in global supply chains and production processes, are vulnerable to flood risks: they are crisis-prone critical infrastructure (CI) systems. However, the governance of their flood resilience involves many different private and public actors in a complex institutional environment and there is no scholarly consensus about how resilience can be successfully governed. We investigate the governance of flood resilience at the Port of Rotterdam (PoR) from an institutional perspective, by studying institutional arrangements for flood resilience within and across vertical, horizontal and territorial dimensions to elucidate the strengths and ongoing challenges of shaping the port's flood resilience. We conducted semi-structured expert interviews ( n 0.167em=0.167em17) and an analysis of policy documents and legislation ( n 0.167em=0.167em33) relating to flood risk management and CI protection. We find that the institutional design for flood resilience in the Netherlands consists of a complex matrix of responsibilities, capacities and plans. While coordination is visible in the shared visions and strategies for flood resilience developed at different policy levels and domains, we find fragmentation and persisting institutional challenges, including siloed governance approaches, knowledge gaps and blurred distribution of responsibilities; these are significant barriers to enhancing flood resilience for CIs and port–city relationships.
Keywords: 380; Flood resilience; Seaport; Governance challenges; Institutionalisation; Critical infrastructures